1990
DOI: 10.1037/0097-7403.16.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical structures: Chunking by food type facilitates spatial memory.

Abstract: Three experiments assessed the ability of male Sprague-Dawley rats to organize the spatial locations of different food types in a hierarchical manner to maximize the efficiency of working memory. Independent groups were exposed, on a 12-arm radial maze, to baiting arrangements varying in the stability of the pattern and type of food used as bait. Training rats with stable, differentiable baiting arrangements produced increased accuracy in choice performance, hierarchically ordered patterns of choice selection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 30 publications
9
78
1
1
Order By: Relevance
“…We propose that this is because the flight pattern connecting these neighboring flowers was simpler than that connecting more dispersed flowers. Although it might be the case that we are reinforcing a natural tendency to visit adjacent flowers, it may also be that the birds are able to "chunk" the neighboring flowers more easily, and therefore, remembering three flowers together is easier than recalling three spatially disparate flowers (Dallal & Meck, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…We propose that this is because the flight pattern connecting these neighboring flowers was simpler than that connecting more dispersed flowers. Although it might be the case that we are reinforcing a natural tendency to visit adjacent flowers, it may also be that the birds are able to "chunk" the neighboring flowers more easily, and therefore, remembering three flowers together is easier than recalling three spatially disparate flowers (Dallal & Meck, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…In summary, the present series of experiments add to a growing body of findings showing that choline availability during ED 12-17, the time of origin of cholinergic neurons in the rat basal forebrain (Semba and Fibiger 1988) is crucial for the development of a number of cognitive abilities that are dependent, in part, on cholinergic input to and relational processing by the hippocampus (e.g., Dallal and Meck 1990;Halford et al 1998;O'Reilly and Rudy 2001;Meck and Williams 2003;Dupret et al 2008). It is important to note, however, that although prenatal choline availability has been shown to primarily affect the septum and hippocampus (e.g., Meck and Williams 2003;Mellott et al 2007b;Meck et al 2008), other brain regions such as the frontal cortex and striatum are also modified by these treatments and may contribute to some of the observed behavioral effects (e.g., Meck et al 1989;Sandstrom et al 2002;Mellott et al 2007a;Nag et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that when choline is administered at levels higher than normal to pregnant rats during embryonic days (ED) 12-17, the adult offspring showed enhanced spatial and temporal memory (Meck and Williams 2003). Specifically, rats given this prenatal-choline supplementation made fewer errors when tested on a radial-arm maze (Meck et al , 1989Meck and Williams 1999) and are able to chunk more information in spatial memory that helps them identify multiple-reward baiting patterns (Dallal and Meck 1990;Meck and Williams 1997b). Similarly, when challenged with tasks that require the ability to remember durations in the seconds-to-minutes range, prenatal choline-supplemented rats produced more precise timing functions and are better able to time multiple durations simultaneously compared with control rats (Meck and Williams 1997a,c;Cheng et al 2006b).…”
mentioning
confidence: 99%